Estimated Rice Sales at Perum Bulog Sub Divre Medan using the Double Exponential Smoothing Method - Windy Esti Andari; Diyah Nurhayati (International Journal of Science and Mathematics Education, 2024)
The estimated rice sales at Perum Bulog Sub Divre Medan is crucial information in planning and managing rice supplies. In this study, we apply the Double Exponential Smoothing forecasting method to estimate rice sales at Perum Bulog Sub Divre Medan. This approach allows us to identify complex sales patterns and generate accurate forecasts to aid in informed decision making. We use historical rice sales data to train a forecasting model and evaluate its performance. Experimental results show that the Double Exponential Smoothing method can provide reliable estimates of rice sales, with a satisfactory level of accuracy. The implications of these findings are discussed in the context of inventory management and operational planning of Perum Bulog Sub Divre Medan.